Quantum mechanics problems and solutions - Wan, Kong (Singapore : Jenny Stanford Publishing, 2019)
This is a companion volume to K. Kong Wan's textbook Quantum Mechanics: A Fundamental Approach, published in 2019 by Jenny Stanford Publishing. The book contains more than 240 exercises and problems listed at the end of most chapters. This essential manual presents full solutions to all the exercises and problems that are designed to help the reader master the material in the textbook. Mastery of the material in the book would contribute greatly to the understanding of the concepts and formalism of quantum mechanics.
24 Direct Sums and Tensor Products of Hilbert Spaces and Operators -- 25 Pure States -- 26 Observables and Their Values -- 27 Canonical Quantisation -- 28 States, Observables and Probability Distributions -- 29 Time Evolution -- 30 On States after Measurement -- 31 Pure and Mixed States -- 32 Superselection Rules -- 33 Many-Particle Systems -- 34 Conceptual Issues -- 35 Harmonic and Isotropic Oscillators -- 36 Angular Momenta -- 37 Particles in Static Magnetic Fields -- Bibliography
OCLC-licensed vendor bibliographic record.
Keywords: Quantum theory; SCIENCE / Chemistry / Physical & Theoretical; SCIENCE / Mathematical Physics